Pyruvate decarboxylase in minimally processed young palm cladode (Research, Society and Development, 2020)
The palm is a cactaceous of great global importance, being the young cladodes minimally processed a viable alternative consumption for cooking. Among the studied palm variables, enzymes play a major role in the post-harvest quality of these species, generating oxidation and influencing the sensory attributes of cladodes. Therefore, the objective was to estimate the pyruvate decarboxylase activity in young cladodes of 'Tiny' palms - Nopalea cochenilifera and 'Ear Mexican Elephant' - Opuntia tuna minimally processed. The experiment was conducted in the Laboratory of Chemistry, Biochemistry and Food Analysis Center of Science and Technology Agrifood the Federal University of Campina Grande, Campus Pombal, Paraíba. The young cladodes were minimally processed and the analyzes were performed immediately after processing, with 24 and 48 hours of incubation under controlled temperature (22 ± 2°C). The analyzes performed were activity of the enzyme pyruvate decarboxylase (PDC), pH, soluble solids, titratable acidity, ratio, soluble sugars, total chlorophyll, total carotenoids, ascorbic acid and phenolic compounds. There was enzymatic activity of pyruvate decarboxylase from young minimally processed cladodes for the species studied, with greater activity in the cladodes of the species 'Tiny'.